E-Worksheet to Improve Critical Thinking and Scientific Argumentation Skills: A Systematic Literature Review - Sudirman; Ruth Rize Paas Megahati S; Risnawati Agustin; Ella Masita; Nuridin Widya Pranoto (Jurnal Penelitian Pendidikan IPA, 2024)
Using e-worksheets will provide students with the opportunity to actively participate in the process of technological development in an increasingly rapid world, be able to think critically, and enable students to argue scientifically. E-worksheet is a form of E-worksheet that is done digitally and carried out systematically and continuously over a certain period. E-worksheets can improve critical thinking skills and scientific argumentation. E-worksheets can be created and designed according to needs in the learning process. The student activity sheet contains tasks that must be carried out by students. Where the research aims to examine E-worksheets to Improve Critical Thinking Abilities and Scientific Argumentation: A Systematic Literature review. The review was conducted based on state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research explain that: The types of teaching materials in learning are printed teaching materials, audio teaching materials, audio-visual teaching materials, interactive multimedia teaching materials, and web-based teaching materials; Various forms of E-worksheets: E-worksheets that help students discover a concept, practice, integrate various concepts that have been discovered, study guides, practical instructions; Function of E-worksheet: functions as a medium, learning tool, Critical Thinking Skills and Scientific Argumentation.